RESTORATIVE JUSTICE TERHADAP PENGGUNA NARKOTIKA DAN OBAT OBATAN BERBAHAYA - Hatarto Pakpahan (Jurnal Cakrawala Hukum, 2015)
Narcotic user who does not involved with illegal narcotics dealer based on Narcotic Act Number 35 of 2009, isverdicted by prison criminal sanction. Those sanction is based on principle with the criminal act did by otherperpetrator with verdict of another Article on the act as well. This is kind of ironic, because narcotic user is notincluded in drug cartel is the real victim of narcotic misuse, so that the criminal sanction that ideally appliedshould be the one who represent restorative justice value. Restorating in term of healing based on narcotic userin which they are the sick victim to be healed not prisoned